A pesticide banned in the European Union over a decade ago is still present in raptors in Poland. (8th December 2020) - Kitowski, Ignacy; Łopucki, Rafał; Stachniuk, Anna; Fornal, Emilia
Summary: The prevalent pesticide carbofuran was banned in the European Union (EU) in 2008; however, the extent of its actual elimination from the environment has been little studied. The presence of this pesticide in the livers of the protected raptors the white-tailed eagle ( Haliaeetus albicilla ) and the common buzzard ( Buteo buteo ) was monitored in Poland from 2008 to 2019 using liquid chromatography with tandem mass spectrometry analysis and data from government institutions. Carbofuran residues were detected in the liver samples of the analysed raptors throughout the period studied. In total, carbofuran was detected in the livers of 33% of the eagles and 54% of the buzzards; concentrations were in the ranges of 11–699 and 14–1890 μg kg –1 of dry matter, respectively. Effective measures to eliminate banned pesticides from the market more efficiently are required.